2010
DOI: 10.1038/ejcn.2010.185
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the bioavailability of ferrous fumarate and ferrous sulfate in non-anemic Mexican women and children consuming a sweetened maize and milk drink

Abstract: Background/Objectives: Ferrous fumarate is recommended for the fortification of complementary foods based on similar iron absorption to ferrous sulfate in adults. Two recent studies in young children have reported that it is only 30% as well absorbed as ferrous sulfate. The objective of this study was to compare iron absorption from ferrous fumarate and ferrous sulfate in infants, young children and mothers. Subjects/Methods: Non-anemic Mexican infants (6-24 months), young children (2-5 years) and adult women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…Previous studies have shown mixed results when comparing absorption of these two iron salts, with some reporting ferrous sulfate is better absorbed [12,31], while others report that the two are equally absorbed [32][33][34][35][36]. Results might differ due to differences in study population, the iron status of participants, the fortification levels or the nature of test meals provided by these studies.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown mixed results when comparing absorption of these two iron salts, with some reporting ferrous sulfate is better absorbed [12,31], while others report that the two are equally absorbed [32][33][34][35][36]. Results might differ due to differences in study population, the iron status of participants, the fortification levels or the nature of test meals provided by these studies.…”
Section: Discussionmentioning
confidence: 73%
“…Due to lower solubility, ferric iron is less bioavailable than ferrous iron [64]. Ferrous fumarate, ferrous sulphate, and ferrous gluconate are the major types of ferrous iron supplements, with comparable bioavailability [6567]. The estimated absorption rate of the ferrous salts was found to be 10–15%, without significant differences among the three major formulations, in a small RCT [68].…”
Section: Oral Iron Supplementationmentioning
confidence: 99%
“…[22] In two studies comparing the absorption of ferrous sulfate and ferrous fumarate from fortified milk-based drinks, one study found that ferrous sulfate was better absorbed than ferrous fumarate,[23] while absorption of ferrous sulfate and ferrous fumarate did not differ significantly in the second study. [24] Given the significant effects that the type of salt may have on in vitro dissolution, ferrous sulfate-containing supplements such as Folifer® may therefore be a better choice for iron/folic acid supplementation in individuals at risk of iron/folate deficiencies, such as pregnant and lactating women.…”
Section: Discussionmentioning
confidence: 99%